Naxal Insurgency in India: Managing Conflict through Empowerment - Ahlawat, Dalbir (International Journal of Criminology and Sociology, 2024)
The election of an indigenous (Adivasi) lady as the President of India added a new dynamic to the centuries-old Naxal insurgency in India. Not receiving a fair deal after India’s independence, the Naxals adopted Maoist ideology. By 2010 the insurgency engulfed one-third of India and posed a serious security challenge. Since then, the Congress and Bharatiya Janata Party (BJP) governments have adopted different strategies to curtail the insurgency, but it still persists. Against this backdrop, this article briefly discusses the historical antecedents; delineates in detail the operational strategies adopted by the Naxals, the counter-insurgency strategies adopted by the Congress and BJP governments; developmental challenges faced by the Adivasis; and suggests recommendations for how the President of India, an Adivasi herself, can be instrumental in containing the Naxal insurgency threats through empowerment.